2017
DOI: 10.4300/jgme-d-16-00167.1
|View full text |Cite
|
Sign up to set email alerts
|

Successful Implementation of a Direct Observation Program in an Ambulatory Block Rotation

Abstract: Background Direct observation of clinical skills is a cornerstone of competency-based education and training. Ensuring direct observation in a consistent fashion has been a significant challenge for residency programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…11 Previous studies examining direct observation in the outpatient setting have shown acceptability among faculty and changes in practice. 12,13 A longitudinal coaching program in pediatrics was associated with an increase in integration of resident self-assessment into feedback sessions and improved resident confidence in faculty feedback, 18 and other models of direct observation, such as videotaping, have shown promise in improving the quality of feedback. 19 We found differences between resident self-evaluation and faculty-observed performance, consistent with previous literature showing poor rates of physician self-assessment of clinical skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Previous studies examining direct observation in the outpatient setting have shown acceptability among faculty and changes in practice. 12,13 A longitudinal coaching program in pediatrics was associated with an increase in integration of resident self-assessment into feedback sessions and improved resident confidence in faculty feedback, 18 and other models of direct observation, such as videotaping, have shown promise in improving the quality of feedback. 19 We found differences between resident self-evaluation and faculty-observed performance, consistent with previous literature showing poor rates of physician self-assessment of clinical skills.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory practice is a crucial aspect of internal medicine residency training in which direct observation is often limited because of encounters occurring behind closed doors with several residents supervised by 1 attending physician. Data suggested that structured episodes of direct observation in ambulatory settings might be valuable for educational assessment and resident skills development, 12,13 although no published studies, to our knowledge, have examined the benefits of adding structured coaching in this clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Direct observation represents the major way to assess the professional competence of trainees. [1][2][3][4][5][6] With few models in the literature on which to base one's observations, the enhanced BSO model we have presented gave faculty a tool they can use to observe trainees more frequently and provided an opportunity to give more specific and effective feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Previous direct observation and coaching interventions in the outpatient setting have demonstrated acceptability among residents and faculty, improved resident confidence in faculty feedback, and better identification of blind spots in resident self-assessment [11,13,14]. This paper adds to this sparse literature by describing how this is grounded in a conceptual framework and providing some evidence for its educational value in changing behaviors.…”
Section: Critical Reflectionmentioning
confidence: 96%